2013
DOI: 10.1093/jrr/rrt007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a novel UVB-tolerant rice mutant obtained by exposure to carbon-ion beams

Abstract: UVB radiation suppresses photosynthesis and protein biosynthesis in plants, which in turn decreases growth and productivity. Here, an ultraviolet-B (UVB)-tolerant rice mutant, utr319 (UV Tolerant Rice 319), was isolated from a mutagenized population derived from 2500 M1 seeds (of the UVB-resistant cultivar ‘Sasanishiki’) that were exposed to carbon ions. The utr319 mutant was more tolerant to UVB than the wild type. Neither the levels of UVB-induced cyclobutane pyrimidine dimers (CPDs) or (6-4) pyrimidine-pyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In previous studies, Ishikawa et al 37) reported that three lowcadmium-accumulating rice mutant lines induced by carbon ions possessed a 1-bp deletion, <227-kb deletion, and 433-bp insertion accompanied with an insertion of mPingA1, a kind of transposable element in rice, respectively. Takano et al 38) reported that they found a 45,419-bp-deletion in the ultraviolet-B-tolerant rice mutant induced by carbon ions. Although there is not sufficient information to draw conclusions at this point, these data, with ours included, suggest that carbon ions are possibly a mutagen that can induce various types of mutations such as small deletion, large deletion, and translocation in the rice genome, as in the case of Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Ishikawa et al 37) reported that three lowcadmium-accumulating rice mutant lines induced by carbon ions possessed a 1-bp deletion, <227-kb deletion, and 433-bp insertion accompanied with an insertion of mPingA1, a kind of transposable element in rice, respectively. Takano et al 38) reported that they found a 45,419-bp-deletion in the ultraviolet-B-tolerant rice mutant induced by carbon ions. Although there is not sufficient information to draw conclusions at this point, these data, with ours included, suggest that carbon ions are possibly a mutagen that can induce various types of mutations such as small deletion, large deletion, and translocation in the rice genome, as in the case of Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is predicted that ion beams induce marked mutations, including deletions, insertions, inversions, duplications and/or translocations. Supporting this idea, several mutant plants carrying an inversion [ 12 , 17 , 29 ] or deletion [ 32 , 33 ] within a given chromosome have been reported. Moreover, cytological analysis using tobacco cultured cells has shown that abnormal chromosomes such as minichromosomes or bridge structures are induced by ion beams [ 34 , 35 ], suggesting that ion beams induced aberrations involving plural chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, through comparative genomic hybridization (array CGH) analysis between wild‐type and utr319 rice mutant induced by carbon ions, Takano et al . () found that Os07g026510 gene in rice contributed to ultraviolet‐B (UVB: 280–320 nm) tolerance. Using DNA microarray techniques, Hwang et al .…”
Section: Application Of Omics Technology To Investigate the Mechanismmentioning
confidence: 99%
“…Presently, a series of studies have been performed to investigate the mechanisms for desired phenotype plant mutants induced by heave-ion irradiation. For example, through comparative genomic hybridization (array CGH) analysis between wild-type and utr319 rice mutant induced by carbon ions, Takano et al (2013) found that Os07g026510 gene in rice contributed to ultraviolet-B (UVB: 280-320 nm) tolerance. Using DNA microarray techniques, Hwang et al (2014) found that 220 MeV l À1 carbon ions (LET = 107 keV l À1 ) can induce up-regulated gene expression related to sugar and starch accumulation in rice.…”
Section: High-throughput System For Screening Positive Microbial Strainmentioning
confidence: 99%